Memorialising and Commemorating Traumatic Past: Diary of a Guerrilla Girl - Pokharel, Badri Prasad (KMC Research Journal, 2019)
This article makes an attempt to analyze Tara Rai’s Chhapamar Yubatiko Dayari (The Diary of a Guerrilla Girl) with the help of trauma theory. It is a memoir which unfolds many hidden parts of a combatant as his/her testimony to signify the traumatic memory. Past events related to war and conflicts always bring a horrible consequence to the survivors who, if anything can, remember these historical events as an act of witnessing the painful traumatic events as a psychological need and a social duty to reminisce those who died in the battle. Testimony, expressed about those events would bring afore the facts which, otherwise, may not be known. In doing so, I have used the critical insights of Caruth and other trauma theorists to illustrate the historical role in understanding the psychological response to war trauma in the form of testimony.  It is important to elucidate the social factors which play a pivotal role in psychological understanding and building together to develop the concept of the personal narrative.